La movilidad de los grupos sociales residentes en la ciudad de Santa Rosa, desde 1980 hasta el 2005 - Espinoza Espinoza, Ángel (2009)
The investigation on the mobility of social groups Santa Rosa from 1980 to 2005. These social groups object of our study are marginal urban seats, generated by migration, and establish their social mobility and determine their quality of life. Therefore migrant define as the person moves geographically from one place to another, usually for economic or social causes, experiencing many positive and negative impacts on society of this city transformations. As social mobility also is the journey made within the social structure both horizontally and vertically of the city of Santa Rosa. While it is true, these families came in search of work, better opportunities for improvement, to achieve a better quality of life and access to a different and positive education. They also determined the population growth of marginal urban areas and it is clear that a segment of the migrant population was likely to be vulnerable to social problems